Research on Contribution Rate of Independent Innovation to Economic Growth: Evidence from Changshou District of Chongqing City in China - Xing Wang (Hindawi Limited, 2021)
Using the data of Chongqing Statistical Yearbooks from 2015 to 2020 and based on the Cobb-Douglas production function of Solow residual method, this paper constructs a functional relationship model among GDP, employment number, fixed asset investment, and economic growth. The contribution rate of independent innovation in Changshou District of Chongqing City is improved by using polynomial distributed lag model. Besides, the contribution rate of independent innovation in Shapingba District, Yuzhong District, Jiangbei District, and Beibei District of Chongqing City is compared with that in Changshou District. The research shows that, overall, independent innovation contributes a lot to the economic growth of Changshou District, but its contribution rate is in a slowly declining state. The government needs to take active measures to improve the level of independent innovation and promote the regional economic growth.